Editorial - Apivatthakakul, MD, Theerachai (Journal of Southeast Asian Orthopaedics, 2022)
The Thai Journal of Orthopaedic Surgery Volume 43 / Number 3-4 July-October 2019 is published in October 2019. This issue consists of many interesting articles which is commonly used in our daily practice and some innovation from our member. The first one is the common fracture in elderly “ Colles’ fractures” the effect of the hematoma block. Second, the innovation using smart phone to assist acetabular cup placement. Third, the outcome of short segment fixation in thoracolumbar fractures and the last is skin numbness after total knee arthroplasty. Our journal is making progress in a positive way with supporting from the RCOST committee and all RCOST members who submit their valuable work in Orthopaedic field to demonstrated the up to date knowledge and skill or basic knowledge of Administration system to improve national policy in treating Orthopaedic patients.